Mammal watching tourism in the Pantanal - Tortato, Fernando Rodrigo; Ribas, Carolina; Concone, Henrique Villas Boas; Hoogesteijn, Rafael (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Wildlife tourism has been gradually increasing in several world regions, especially in countries with high biodiversities, such as Brazil. This activity seeks to observe charismatic species in the free life, among which many are mammals. The activity is still underdeveloped in Brazil, but the Pantanal is the biome with the greatest potential for expanding and consolidating this type of tourism. The Pantanal is considered a Brazilian savannah, with an abundance of easily observed wildlife, including large vertebrates such as peccaries, capybaras, giant otters, and even jaguars. Wildlife watching tourism in this biome has increased in recent years, mainly in the northern region, in the Pantanal of Cuiabá, and to the south in the Pantanal of Miranda and Aquidauana. In this chapter, we discuss the characteristics of the wildlife watching activity in the Pantanal, the main species observed, the laws and rules already established, the existing problems, and address the importance of tourism as an economic activity for the sustainable development of the Pantanal.
Keywords: Wetlands; Brazil; State legislation; Mammals; Wildlife tourism